"Radical Bilingualism" in Fouad Laroui's Une année chez les Français. Issue 1 (1st January 2022) - AGAR, TRUDY
Abstract : This article considers language practices in Une année chez les Français, a 2010 novel by the multilingual Moroccan writer Fouad Laroui, by drawing on Abdelkébir Khatibi's concept of "radical bilingualism" and on Mikhail Bakhtin's understanding of "polyglossia". It focuses on ways in which French cultural and linguistic domination is both reinforced and contested by a range of textual and linguistic strategies, including relexification, code-switching, translation, neologism and word play. Laroui's radical bilingualism will be shown to blur language borders and destabilize the notion of language purity, while creating a literary space that is playful, dynamic, plural and unstable. Radical bilingualism in this novel will be revealed as a subversive strategy that Laroui uses to engage in a "double critique" of French neo-colonial domination and privilege and of Moroccan nationalist essentialism.